Gerakan Melawan Arus melalui Karya Sastra: Kajian Sosiologi Sastra - FS Aristyo Nugroho; Nurdien Harry Kistanto (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2021)
Zines have been around since 1940. Zines cover topics as broad as fan fiction, politics, poetry, art, design, ephemera, personal journals, social theory, feminism, punk, and even sexual content that is far beyond the mainstream. Zine is one of the most trusted magazines when it comes to writing about alternative music and culture. In Indonesia, there are many zines. Zine is a print publication and became known in Indonesia in 1995. One of the leading writers in Indonesian punk zines is Aditya Rahman Yani, commonly known as Aditya Abdurahmman (Aik). The researcher  will discuss the sociology of the author of this book and zine and all about punk zine in Indonesia. The method that will be used by the author in the analysis is descriptive qualitative. The researcher finds that Aditya is now a hard, firm person, and holds his ideology in writing. Punk zines in Indonesia will always exist with changing models according to the ideology of the writers.